KUALITAS SEMEN SEGAR KAMBING BOER PADA TEMPERATUR PENYIMPANAN 4 OC DENGAN MENGGUNAKAN PENGENCER SITRAT DAN SUPLEMENTASI SUSU KEDELAI BUBUK - Rahayu, Winda; W.M, Agung Pramana (Biotropika: Journal of Tropical Biology, 2014)
ABSTRACT The objective of this research was to know the influence of soybean milk powder diluents based on concentration (2%, 4%,6%) in citrate diluent to motility, viability, abnormality and membrane integrity of spermatozoa based on long duration storage (0 hours, 24 hours, 72 hours, 120 hours). This research using diluent medium based on vegetable medium (lechitin) is andromed (K+), soybean milk in diluent citrate with concentrations of 0% (K-), 2% (F1), 4% (F2), and 6% (F3). The characterization of predilution were observed such as volume, color, consistency, pH, mass motility, individual motility, viability, concentration, and abnormality. Next step dilution based on treatment with each of the threeÂ recurrence and performed storage at temperature of 4ËC. The next of post storage were observed such as sperm viability, motility, abnormality and membrane integrity. Data were analyzed using two way ANOVA in factorial completely randomized design with SPSS version 16.0 and continued with Tukey test. The results showed that a significant difference (P<0.05)Â to K+, F1, and F2 diluent to K- and F3 diluent. The presence of lechitin content of soybean milk can protect spermatozoa from cold shock during storage at a temperature of 4ËC. The concentration of soy milk powder high possibility changes to pH of the media and influenced of osmotic presure on sperm membrane decrease of the sperm quality during storage. Key word: Lechitin, plasma membrane, soybean milk